The process of circulation in quesnay's Tableau Économique (2008)
At the end of the 17th century capitalism had become the new social and economic order in northern Western Europe. Ever since the trading channels through which money and commodities change hands between the different agents, the actual sequence of these all-comprising monetary exchange processes, and the intertwining of the processes of production and circulation have always been a central issue in heterodox economic thought. The paper discusses Quesnay's contribution to the theoretical foundation of the social process of circulation of capital in a monetary production economy in the Tableau économique. Additionally, the accounting dynamics of the circulation process of the agricultural kingdom is described by means of system of credit-debit tables currently used by German authors.